Labour migration, marriage and family life in a Ciskei village - Manona, Cecil Wele (Rhodes University, Faculty of Humanities, Department of Anthropology, 1981)
From introduction: The aim of this thesis is to describe and analyse the effects of labour migration on marriage and family life. The field material is from Burnshill, a village situated in the Keiskammahoek district in the Ciskei. Keiskammahoek is bounded on the East by the districts of King William's Town and Stutterheim, on the West and South by Middledrift and on the North by Cathcart. The inhabitants of Burnshill are overwhelmingly Xhosa and Mfengu (the main ethnic groups in the Ciskei) but also include a small proportion of people whose clans are of Mpondo and Thembu origin. This village has undergone extensive change. As we shall show later, it was settled de novo by the Mfengu and the Xhosa during the second half of the past century. This is one of the reasons why it lacks the homogeneity and continuity of cultural tradition which are predominant features of long-established communities.
Keywords: Migrant labor -- Social aspects -- South Africa -- Ciskei